Cellulose nanocrystals of variable sulfation degrees can sequester specific platelet lysate-derived biomolecules to modulate stem cell response - Mendes, B. B. (2020)
The surface chemistry of cellulose nanocrystals was engineered to show variable sulfation degrees, which was exploited to modulate platelet lysate-derived biomolecule sequestration and presentation. The protein coronas developed on CNC surfaces were characterized and it was demonstrated how they promote different signaling effects on human adipose-derived stem cell behavior.